1998
DOI: 10.1002/(sici)1097-0223(1998100)18:10<1023::aid-pd402>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal karyotypes in semi-direct chorionic villus preparations of women with different cytogenetic risks

Abstract: Among 3499 cytogenetically investigated semi‐direct chorionic villus samples, 219 (6·3 per cent) abnormal karyotypes were encountered. The karyotypes were considered certainly abnormal (generalized abnormal with high probability) in 109 cases (3·1 per cent), and in 110 cases (3·1 per cent) uncertainly abnormal (potentially confined to the placenta), requiring further investigation. Of these 110 uncertain abnormalities, the cytogenetic result turned out to be finally abnormal representing generalized abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 55 publications
3
27
4
Order By: Relevance
“…The negative predictive value is 100% since we had no cases with false negative results. The positive predictive value of 66% in this study is comparable to the results of Breed et al (1990), the US collaborative study (Ledbetter et al, 1992) and Los et al (1998), which were 64, 68.4 and 67.8%, respectively. The positive predictive value of 75% in the EUCROMIC study (Hahnemann and Vejerslev, 1997a) is somewhat higher.…”
Section: Discussionsupporting
confidence: 81%
“…The negative predictive value is 100% since we had no cases with false negative results. The positive predictive value of 66% in this study is comparable to the results of Breed et al (1990), the US collaborative study (Ledbetter et al, 1992) and Los et al (1998), which were 64, 68.4 and 67.8%, respectively. The positive predictive value of 75% in the EUCROMIC study (Hahnemann and Vejerslev, 1997a) is somewhat higher.…”
Section: Discussionsupporting
confidence: 81%
“…So in only 3.3% of the cases with positive NIPT results, CVS will not give definitive results and further testing in amniotic fluid will be necessary. This figure does not appear to be very different from the situation where CVS is done due to high aneuploidy risk (women with abnormal first trimester screening results or advanced maternal age), where circa 2% of the cases require follow up karyotyping in amniotic fluid if only STC-villi are investigated [11]. Therefore, it seems to be appropriate to offer CVS as a confirmatory test if NIPT is positive for trisomy 13, 18, or 21 ( Figure 2).…”
Section: Syncytiotrophoblastmentioning
confidence: 96%
“…Since Flori et al [10] showed that the cellfree fetal DNA in maternal plasma is derived from the outer cell layer of CV, the cytotrophoblast, detection of CPM with NIPT is to be expected at the same rate as is found with cytogenetic investigations of the cytotrophoblast of CV. This showed to be~2% in high-risk pregnancies in our center [11]. Therefore, it is recommended to confirm a positive NIPT result by invasive prenatal testing, preferably by amniocentesis (a joint European Society of Human Genetics [ESHG]/American Society of Human Genetics [ASHG] position statement) [12].…”
Section: Biological Origin Of False Positive Niptmentioning
confidence: 96%
See 2 more Smart Citations